2007
DOI: 10.1542/peds.2006-1805
|View full text |Cite
|
Sign up to set email alerts
|

Improving Asthma-Related Health Outcomes Among Low-Income, Multiethnic, School-aged Children: Results of a Demonstration Project That Combined Continuous Quality Improvement and Community Health Worker Strategies

Abstract: The demonstration produced major improvements in asthma-related care processes and clinical outcomes. Closer adherence to the demonstration model was directly associated with better outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
66
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 33 publications
0
66
0
Order By: Relevance
“…Two of four RCTs demonstrated a significant decrease relative to control, 40,53 and two showed no significant decrease relative to control. 54,55 Of the four pre-post studies measuring this outcome, three demonstrated a statistically significant decrease, 41,44,45 and one showed a non-significant increase. 46 …”
Section: Emergency Department Visitsmentioning
confidence: 93%
See 4 more Smart Citations
“…Two of four RCTs demonstrated a significant decrease relative to control, 40,53 and two showed no significant decrease relative to control. 54,55 Of the four pre-post studies measuring this outcome, three demonstrated a statistically significant decrease, 41,44,45 and one showed a non-significant increase. 46 …”
Section: Emergency Department Visitsmentioning
confidence: 93%
“…[33][34][35] Five showed no significant difference in ED visits. [36][37][38][39][40] Of the eight pre-post studies, five showed a significant decrease in ED visits relative to a baseline measurement, [41][42][43][44][45] and one had no significant decrease. 46 Two pre-post studies did not indicate statistical significance; of these, one intervention resulted in a decrease in ED visits 47 and one in an increase in ED visits.…”
Section: Emergency Department Visitsmentioning
confidence: 94%
See 3 more Smart Citations